Standard specification for Pressure Vessel Plates, Carbon Steel, for Moderate- and Lower-Temperature Service (American Society of Testing Materials, 2006)
This specification covers carbon steel plates intended primarily for service in welded pressure vessels where improved notch toughness is important.